Ruthenium-catalyzed stereo- and chemoselective oxidative coupling of vinyl ketones: efficient access to (E, E)-1, 6-dioxo-2, 4-dienes. Issue 18 (15th February 2022) - Dethe, Dattatraya H.; Nirpal, Appasaheb K.; Beeralingappa, Nagabhushana C.; Kumar, Vimlesh; Srivastava, Aparna; Mishra, Kunj B.; Bhat, Arsheed A.
Abstract : A Ru-catalyzed direct oxidative coupling reaction of vinyl ketones was developed. Abstract : A Ru-catalyzed direct oxidative coupling reaction of vinyl ketones was developed. It offers a straightforward and atom-economical protocol for the synthesis of functionalized ( E, E )-1, 6-dioxo-2, 4-diene derivatives in moderate to good yields with excellent stereo- and chemoselectivities. In addition, the synthetic utility of this method was further demonstrated by its application to the synthesis of bioactive natural products such as (7 E, 9 E )-henicosa-7, 9-diene-6, 11-dione (sex pheromone), ostopanic acid (plant anticancer agent), JA (anti-tumor agent) and the southern part (C1–C13) of the antibiotic macrolactin-T.